Labor Integration with Persons with Disabilities in Public Institutions in Romania - Veronica JUNJAN; Mugur CIUMĂGEANU; Ioana MICLUŢIA; Ioana CRĂCIUN (Transylvanian Review of Administrative Sciences, 2011)
This research aims to investigate the extent to which the legislation aimed to improve and support the labor reinsertion of persons with disabilities is implemented by public institutions. The results suggest that the law provisions concerning labor reinsertion of persons with disabilities are followed to a lower extent than might be expected. Approximately 7% of the organizations that answered this survey and have more than 50 employees do not implement any of the provisions of the law, therefore having no employed persons with disabilities, not paying the contributions to the state budget, and without contracting of services from the protected workplaces. The other institutions employ fewer persons with disabilities than they should do (about 1% comparing to the 4% required by the law). Almost half of the public institutions prefer to use the second option provided by the law, namely to pay the contribution to the state budget instead of hiring persons with disabilities. Additional research is needed to extend this exploratory investigation.